2014
DOI: 10.1167/iovs.14-14054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cataract Surgery on Sleep in Patients Receiving Either Ultraviolet-Blocking or Blue-Filtering Intraocular Lens Implants

Abstract: Overall sleep quality and sleep latency improves after removal of cataract irrespective of the type of IOL implanted. These data show that implantation of BF-IOL does not have a negative impact on the sleep-wake cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 23 publications
2
59
0
1
Order By: Relevance
“…Sleep quality improved significantly following cataract surgery in the short term for the entire cohort, irrespective of the type of lens implanted. 17 Schmoll et al 18 looked at sleep-wake and cognitive reaction times and showed no difference between BFIOL or UVFIOL. The CHUKYO study was designed to evaluate blood pressure and sleep duration after IOL implantation during cataract surgery and to compare different types of IOL.…”
Section: Age-related Macular Degeneration and Iol Typementioning
confidence: 98%
See 4 more Smart Citations
“…Sleep quality improved significantly following cataract surgery in the short term for the entire cohort, irrespective of the type of lens implanted. 17 Schmoll et al 18 looked at sleep-wake and cognitive reaction times and showed no difference between BFIOL or UVFIOL. The CHUKYO study was designed to evaluate blood pressure and sleep duration after IOL implantation during cataract surgery and to compare different types of IOL.…”
Section: Age-related Macular Degeneration and Iol Typementioning
confidence: 98%
“…The SCN in turn regulate circadian biology throughout the body. 17,65 Ocular light input is required to synchronise the body clock to the environmental daynight cycle. 17 It has already been shown in a number of studies that in addition to improving vision, cataract surgery has been shown to lead to an improved sleep-wake pattern.…”
Section: Age-related Macular Degeneration and Iol Typementioning
confidence: 99%
See 3 more Smart Citations